Requisitos para a Construção do Fundeb - José Marcelino de Rezende Pinto (Universidade Estadual Paulista Júlio de Mesquita Filho, 2007)
This paper aims to analyze the financial resources of states and local governments applied on basic education (early childhood education, pre-school, elementary and secondary school). The data gathered from INEP (National Institute for Statistics and Educational Research) and STN (National Budget Office) show that a good amount of federal money will be necessary if the new fund for basic education, FUNDEB, intend to avoid regional disparities and to assure a per pupil cost which gives the guarantee of a minimum standard of school quality as pointed by the Education National Guidelines Law (LDB).